An Analysis of Reciprocal Influence between Advertising Expenditures and Gross Domestic Product - Bayazit, Zeynep; Genc, Elif Guneren (International Journal of Economics and Financial Issues, 2019)
In today's interconnected global economy, advertising plays a crucial role. Advertising, as the most effective marketing communication tool, generates informative value, consumer demand, company visibility, awareness to public, clear market positioning and economic vitality. According to most literature, a company which doesn't neglect marketing obligations and specifically advertising, tends to protect and gain market share and creates a positive brand image and reputation. The present study has explored the relationship between Gross Domestic Product (GDP) and Advertising expenditures (ADspend) according to the development levels of countries. This relation has inspected with using Panel Granger Causality Test, which reformed by Dumitrescu ve Hurin (2012). After that, the study has focused on establishing whether there is a cointegration relationship between GDP and Advertising Expenditures in the selected groups of countries with different types of development levels. Keywords: Advertising, Advertising Expenditures, Panel data models JEL Classifications: M37, O57, C2 DOI: https://doi.org/10.32479/ijefi.7537